THE RISK FACTORS OF HYPERTENSION IN INDONESIA (DATA STUDY OF INDONESIAN FAMILY LIFE SURVEY 5) - Khasanah, Dewi Nur (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACTBackground: Hypertension is a worrying disease, as it often does not cause symptoms. According to WHO, this disease affects 22% of the world's population, while hypertension has affected 25% of the population in Southeast Asia. In Indonesia, the prevalence of hypertensive disease increases from year to year. The suspected risk factors for hypertension are gender, age, genetics, smoking obesity, physical activity, and stress. Purpose: analyze factors that affect the prevalence of hypertension in Indonesia based on Indonesian Family Life Survey (IFLS) 5 data. Method: this study uses secondary data from Indonesia Family Life Survey (IFLS) 5 with a type of analytical observational research with cross sectional design. There were 4790 respondents who sampled research from 34,239 population. The analysis used is bivariate and multivariate. Results: bivariate analysis using chi-square test obtained factors related to hypertension incidence is gender (p=0,000), age (p=0.000), employment status (p=0.003), physical activity (p=0.011); and obesity (p=0.000). While through the test of logistic regression factors that affect hypertension is gender (p=0,000), age(p=0.000), physical activity(p=0.015), and obesity(p=0.000). Conclusion: factors that affect the incidence of hypertension are gender, age, physical activity, and obesity. ABSTRAK Latar Belakang: Hipertensi merupakan penyakit yang menghawatirkan, karena penyakit ini sering tidak menimbulkan gejala. Menurut WHO penyakit ini menyerang 22% penduduk di seluruh dunia, sedangkan penyakit hipertensi telah menyerang 25% penduduk wilayah Asia Tenggara. Di Indonesia, prevalensi penyakit hipertensi meningkat dari tahun ke tahun. Adapun yang diduga menjadi faktor risiko hipertensi yaitu jenis kelamin, umur, genetik, obesitas merokok, aktifitas fisik, dan stress. Tujuan: menganalisis faktor yang mempengaruhi kejadian hipertensi di Indonesia berdasarkan data Indonesian Family Life Survey (IFLS) 5. Metode: penelitian ini menggunakan data sekunder dari Indonesia Family Life Survey (IFLS) 5 dengan jenis penelitian observasional analitik dengan desain cross sectional. Terdapat 4790 responden yang menjadi sampel penelitian dari 34.239 populasi. Analisis yang digunakan adalah bivariat dan multivariat. Hasil: analisis bivariat yang menggunakan uji chi-square didapatkan faktor yang berhubungan dengan kejadian hipertensi adalah jenis kelamin (p=0,000); umur (p=0,000); status pekerjaan (p=0,003); aktifitas fisik (p=0,011); dan obesitas (p=0,000). Sedangkan melalui uji regresi logistik faktor yang berpengaruh terhadap hipertensi adalah jenis kelamin (p=0,000), umur (p=0,000), aktifitas fisik (p=0,015), dan obesitas(p=0,000). Kesimpulan: faktor yang berpengaruh terhadap kejadian hipertensi adalah jenis kelamin, umur, aktifitas fisik, dan obesitas.